"Ngakken Anak" (Adoption) in the Indigenous People of Lampung Pepadun in Gunung Sugih Sub-District, Sub District Gunung Sugih Kabupaten Lampung Tengah - M Dian Antariksa; Risma M. Sinaga; M. Mona Adha (International Journal of Educational and Life Sciences, 2023)
In the indigenous community of Lampung Pepadun in general and especially the people of Gunung Sugih Village, Gunung Sugih District, Central Lampung Regency, there are customs or traditions and must have a son (ragah), whether it is born from the mother's womb or adopted children (adopted). The problems posed in this study are, what factors are the background of Ngakken Anak (adoption), how is the procedure for ngakken Anak (adoption), and what is the position of the child who is angken (adoption). The method used, the main method is descriptive carried out by the questionnaire method, interview or interview of informants, informants are people selected as many as seven (7) informants. The result obtained, is that adoption is carried out if one family (mother, father / husband, wife) does not have children or children, especially sons (ragah). Adoption is also often done because it is to increase the family, or as a result of disasters and disasters. The first procedure for Ngakken Anak (Adoption) is through customary deliberation (Perwatin) and the second is requested directly by the family who will Ngakken Anak (Adoption) to other families, both from their own families and outsiders. While the position of Anak Angken (adoption) is, to complete the arrangement of family completeness, replace the role of the father both in the family and in customary matters, as the successor of future generations and to replace the role and position of the father and family who Ngakken Anak (adopted) and the recipient of inheritance.